Menemukan Kebermaknaan Hidup Melalui Bimbingan dan Konseling Layanan Informasi Berbasis Al-Quran Pada Mahasiswa - Zhila Jannati (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2020)
The purpose of this study was to find out how to find the meaning of life through al-qur'an-based information services for Islamic Guidance and Counseling students at UIN Raden Fatah Palembang. The method used in this research is a qualitative research method. The subjects in this study were 29 students of the Islamic Guidance and Counseling Study Program at UIN Raden Fatah Palembang. Data collection techniques used in this study were interview techniques and observation techniques. The data in this study were analyzed by qualitative descriptive analysis. The results showed that al-qur'an-based information services could enable students of the Islamic Guidance and Counseling Study Program at UIN Raden Fatah Palembang to find the meaning of life which includes (a) understanding of the meaning of life which includes having a purpose in life, (b) understanding of potential self, (c) the ability to act positively in the face of reality, and (d) the ability to build positive social relationships.